Use of a Targeted Urine Proteome Assay (TUPA) to identify protein biomarkers of delayed recovery after kidney transplant. Issue 7 (31st March 2017) - Williams, Kenneth R.; Colangelo, Christopher M.; Hou, Lin; Chung, Lisa; Belcher, Justin M.; Abbott, Thomas; Hall, Isaac E.; Zhao, Hongyu; Cantley, Lloyd G.; Parikh, Chirag R.
Abstract : Purpose: Development of delayed graft function (DGF) following kidney transplant is associated with poor outcomes. An ability to rapidly identify patients with DGF versus those with immediate graft function (IGF) may facilitate the treatment of DGF and the research needed to improve prognosis. The purpose of this study was to use a Targeted Urine Proteome Assay to identify protein biomarkers of delayed recovery from kidney transplant. Experimental design: Potential biomarkers were identified using the Targeted Urine Proteome (MRM) Assay to interrogate the relative DGF/IGF levels of expression of 167 proteins in urine taken 12–18 h after kidney implantation from 21 DGF, 15 SGF (slow graft function), and 16 IGF patients. An iterative Random Forest analysis approach evaluated the relative importance of each biomarker, which was then used to identify an optimum biomarker panel that provided the maximum sensitivity and specificity with the least number of biomarkers. Conclusions and clinical relevance: Four proteins were identified that together distinguished DGF with a sensitivity of 77.4%, specificity of 82.6%, and AUC of 0.891. This panel represents an important step toward identifying DGF at an early stage so that more effective treatments can be developed to improve long‐term graft outcomes.